KONSEP PENDIDIKAN KARAKTER DALAM TINJAUAN HADITS : STUDI ANALISIS TENTANG HADITS-HADITS TARBAWI - M Miftahul Aziz (STAI Ma'had Aly Al-Hikam Malang, 2024)
Character education is the process of instilling certain values ​​and attitudes in students, while providing them with a foundation to develop their own unique characteristics when interacting in society. The emphasis on the concept of character education, in this context, refers to the teachings taught by the Prophet in his hadiths. The Prophet's hadiths include moral and behavioral principles that are considered important to learn and apply in everyday life. This concept is an important focus in research, with the aim of understanding how character is formed, the types of character that exist, and how this character can be applied in everyday life, especially from the perspective of tarbawi hadith. This research aims to provide parents, educators and students with a better understanding of the moral values ​​taught by the Prophet through hadiths, with the hope that they will be able to implement these teachings in the practice of their daily lives. The implementation of these values ​​is expected to create individuals who have good character, morals, and are full of compassion for others.